2005
DOI: 10.1097/01.shk.0000172365.96752.57
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin May Be Useful in the Treatment of Systemic Anaphylaxis in Rabbits

Abstract: Recent studies demonstrate that vasopressin is useful when treating hemorrhagic and septic shock. The effect of vasopressin on systemic anaphylaxis has not been investigated except in clinical case reports. Vasopressin increases blood pressure because of vasoconstriction through the V1 receptor. Thus, we evaluated the effect of vasopressin on circulatory depression and bronchoconstriction provoked by systemic anaphylaxis and survival rates in rabbits. In the first set of experiments, 15 nonsensitized rabbits r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In addition, the idea of an initially preserved CO has also been challenged in several animal models of AS. Although several interspecies differences may exist, impaired myocardial contractility has been demonstrated in lethal models of anaphylaxis (18,19), whereas less severe myocardial depression was observed in nonlethal models (20). In addition, an increase in venous tone in the splanchnic and portal vascular beds, with a presinusoidal contraction within the liver, as well as in the pulmonary veins resulting in a rapid decrease in preload and CO has been reported recently (21Y23).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the idea of an initially preserved CO has also been challenged in several animal models of AS. Although several interspecies differences may exist, impaired myocardial contractility has been demonstrated in lethal models of anaphylaxis (18,19), whereas less severe myocardial depression was observed in nonlethal models (20). In addition, an increase in venous tone in the splanchnic and portal vascular beds, with a presinusoidal contraction within the liver, as well as in the pulmonary veins resulting in a rapid decrease in preload and CO has been reported recently (21Y23).…”
Section: Discussionmentioning
confidence: 94%
“…This study revealed that vasopressin was able to improve survival rates and severe hypotension provoked by systemic anaphylaxis. 25 in conclusion, while the efficacy of vasopression for the treatment of refractory shock has been well documented, experience is limited with this drug in treating anaphylaxis in patients under general anesthesia. We describe the successful use of low-dose vasopressin, in the management of anaphylaxis to rocuronium, in a patient with no previous exposure to neuromuscular blocking drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experimental work provided arguments for the possible use of AVP as therapy of anaphylactic shock. 12,23,24 In other respects, the most recent American guidelines on anaphylaxis 5,25 and several case reports suggested that adding AVP to standard therapy might be considered as a potential therapeutic approach in anaphylactic shock. 9 -11 In the wake of these case reports and taking into account a possible AVP deficiency observed in experimental anaphylactic shock, 12 we compared, in an anesthetized Brown Norway rat model of anaphylactic shock, the survival rate according to the drug injected, epinephrine and/or AVP.…”
Section: Discussionmentioning
confidence: 99%